2023
DOI: 10.1002/tafs.10392
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics model for the nonnative Redside Shiner

Abstract: Objective Redside Shiner Richardsonius balteatus has expanded from its native range in the Pacific Northwest region of North America to establish populations in six other western states. This expansion has fueled concerns regarding competition between Redside Shiner and native species, including salmonids. We developed a bioenergetic model for Redside Shiner, providing a powerful tool to quantify its trophic role in invaded ecosystems and evaluate potential impacts on native species. Methods Mass‐ and temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Bias in bioenergetics model results is a well‐known issue (see Chipps & Wahl, 2008 ; Ney, 1993 ) and the assumption of thermal habitat selection near the optimum has been debated since the early onset of those models (e.g., Bevelheimer, 1990 ; Spigarelli et al., 1982 ). Lab studies comparing growth and consumption rates at various holding temperatures have shown wide variation in results (e.g., Canale, 2014 ; Johnson et al., 2023 ). Comparisons quantifying bias of lab‐obtained thermal versus field‐observed preference of wild populations are rare and indirect (e.g., Brodie et al., 2016 ) and to our knowledge, none exist that include multiple age classes across all seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Bias in bioenergetics model results is a well‐known issue (see Chipps & Wahl, 2008 ; Ney, 1993 ) and the assumption of thermal habitat selection near the optimum has been debated since the early onset of those models (e.g., Bevelheimer, 1990 ; Spigarelli et al., 1982 ). Lab studies comparing growth and consumption rates at various holding temperatures have shown wide variation in results (e.g., Canale, 2014 ; Johnson et al., 2023 ). Comparisons quantifying bias of lab‐obtained thermal versus field‐observed preference of wild populations are rare and indirect (e.g., Brodie et al., 2016 ) and to our knowledge, none exist that include multiple age classes across all seasons.…”
Section: Introductionmentioning
confidence: 99%